2019
DOI: 10.1103/physreva.100.042711
|View full text |Cite
|
Sign up to set email alerts
|

Purely long-range polar molecules composed of identical lanthanide atoms

Abstract: Doubly polar molecules, possessing an electric dipole moment and a magnetic dipole moment, can strongly couple to both an external electric field and a magnetic field, providing unique opportunities to exert full control of the system quantum state at ultracold temperatures. We propose a method for creating a purely long-range doubly polar homonuclear molecule from a pair of strongly magnetic lanthanide atoms, one atom being in its ground level and the other in a superposition of quasi-degenerate opposite-pari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…One presumes the appearance and pattern of chaos may take different forms when states of different angular momentum J are coupled and the molecules become overall more chaotic [3,12]. In this context it is worth noting that even more exotic states of lanthanide dimers have been proposed, which possess large electric dipole moments as well as large magnetic dipole moments, providing additional opportunities for introducing and probing chaos [24,25].…”
Section: Regularities Of the Eigenstatesmentioning
confidence: 99%
“…One presumes the appearance and pattern of chaos may take different forms when states of different angular momentum J are coupled and the molecules become overall more chaotic [3,12]. In this context it is worth noting that even more exotic states of lanthanide dimers have been proposed, which possess large electric dipole moments as well as large magnetic dipole moments, providing additional opportunities for introducing and probing chaos [24,25].…”
Section: Regularities Of the Eigenstatesmentioning
confidence: 99%
“…This spin-forbidden transition facilitated by the spin-orbit coupling between the b 3 Π 0 and the A 1 Σ þ 0 excited states ensures that the spontaneous emission does not hinder the OS efficiency. We calculated the bimolecular long-range potential-energy curves (PECs) from our previous developments [42][43][44][45] safely neglecting the hyperfine structure of the rotational levels (see Supplemental Material [46]). We found that a PEC correlated to the ðj X ¼ 0Þ þ ðj b ¼ 1Þ asymptote possesses a high potential barrier caused by DDI.…”
mentioning
confidence: 99%
“…with L the angular momentum of the mutual rotation of the molecules with the quantum number l (the partial wave), andĤ rot the sum of the rotational Hamiltonian for each molecule. The operatorVðRÞ holds for the long-range interaction between the molecules, including the DDI (∝ R −3 ) and the van der Waals interaction (∝ R −6 ) [42][43][44][45][46]. The laser field Hamiltonian isĤ f , andĤ I is the interaction between the complex and the laser field, depending on the Rabi frequency Ω and the detuning Δ with respect to the ðj X ¼ 0Þ − ðj b ¼ 1Þ transition energy.…”
mentioning
confidence: 99%
See 2 more Smart Citations